Maternal knowledge and attitudes towards rotavirus diarrhea and vaccine acceptance in Yogyakarta, Indonesia: a qualitative study - Mei Neni Sitaresmi; Holly Seale; Anita E. Heywood; Retna Siwi Padmawati; Yati Soenarto; Chandini Raina MacIntyre; Jarir Atthobari (Indonesian Pediatric Society, 2022)
Abstract Background Rotavirus is a leading cause of hospitalized diarrhea cases in Indonesia. Despite the rotavirus vaccine being recommended by the Indonesian Pediatric Society since 2011, it has yet to be been included in the Indonesian national immunization program (NIP) schedule. Objective To explore maternal knowledge of and attitudes towards rotavirus diarrhea, as well as barriers to vaccine acceptance in Yogyakarta, Indonesia. Methods We conducted 26 in-depth interviews in two districts (rural and urban areas) of Yogyakarta Province, Indonesia. Participants included women in their third trimester of pregnancy and mothers of infants younger than 14 weeks. We then proceeded with thematic analysis. Results Participants did not perceive diarrhea as being a priority health problem. Very few had heard of rotavirus diarrhea or were aware of vaccine availability. While participants would accept vaccinating their children against rotavirus, some key barriers impacted vaccine use. As the rotavirus vaccine is not included in the Indonesian NIP, parents perceived it as not essential. Parents were concerned about the safety and benefit of the vaccine due to its perceived newness. Other concerns were cost and halal status. Participants expressed a need for more information on the vaccine's effectiveness and safety, with their primary healthcare providers (HCPs) considered to play the most important role in vaccine acceptance. Conclusions In Yogyakarta, Indonesia, awareness of the seriousness of rotavirus disease and the availability of the rotavirus vaccine is low. Its newness, safety, efficacy, and cost, and doubts about its halal status, were barriers to vaccine acceptance. Information and recommendations from HCPs play an essential role in vaccine acceptance.